Rewilding Pre-Rehabilitation of Post-Industrial Landscape - LEE, Chi Fung Brian; SIU , Kwan Yeung Marco; KAN , Sze Nok Sharon; KONG , Andy Padraig; KWOK , Yuen Ying Venus (MAJ - Malaysia Architectural Journal, 2025)
This research explores the concept of "pre-rehabilitation" for post-industrial landscapes, focusing on the application of rewilding principles as preparatory measures to unlock the ecological value of abandoned industrial sites. The study highlights the potential of rewilding to transform these sites into vibrant public spaces before their redevelopment. By selectively intervening to restore natural processes, such as introducing native plants and ecological corridors, rewilding can enhance biodiversity and create valuable public spaces for recreation. The research also emphasises the economic potential of rewilded sites through eco-tourism, urban agriculture, and renewable energy. Combining ecological restoration, community engagement, and economic viability, rewilding offers a pathway towards a resilient and thriving urban ecology. The research suggests that applying lessons learned from the case study to specified industrial sites in Hong Kong can contribute to sustainable urban development and the revitalisation of post-industrial landscapes.